Reduction of PAPR in MIMO-OFDMA system by using Daoud technique LDPC codes / Nur Farahana Mat Khairi - Mat Khairi, Nur Farahana (2014)
MIMO-OFDMA offers significant high data rates transfer without increasing the bandwidth or transmit power. By adopting diversity coding such as Space Time coding (STC), Space Frequency Coding (SFC), Space Time Frequency Base Coding (STFBC), the major challenge of transmitting information over a long distances can be improved in terms of reliability and security of the data due to ISI and ICI. Low Density Parity Check which is introduced by Gallager in 1962 has attracted much attention to the needs of efficient and reliable coding theory in digital data communication system. In this paper together with STFBC, the simulation of LDPC under 4, 16 and 64 QAM is conducted in 2x2 MMO-OFDMA over Additive White Gaussian Noise (AWGN) and Raleigh fading channel. The propose system is analyzed based on PAPR and BER with signal to noise ratio (SNR). The simulation using Matlab, shows the PAPR comparison, which Daoud LDPC works better in Rayleigh fading channel while in digital modulations the system outperforms with 64-QAM . The performance of LDPC between conventional LDPC and Daoud LDPC are being compared and it is further prove that with STFBC diversity Daoud LDPC achieved a slight improvement in MEMO OFDMA[l].